Corporate capital budgeting: Success factors from a behavioral perspective - Avo Schönbohm; Anastasia Zahn (Technische Universität Kaiserslautern, Lehrstuhl für Unternehmensrechnung und Controlling, 2012)
Capital budgeting or investment decisions have an essential influence on companies' performance. Instead of a rational choice, capital budgeting might be regarded as a process of reality construction. Research suggests that decision makers have only limited control over their own cognitive biases in this construction process. It is in this perspective that this paper intends to answer the following research question: What are behavioral determinants for a successful capital-budgeting decision process? The authors identify and discuss three behavioral success factors (reflective prudence, critical communication and outcome independence) for five stages of the capital budgeting process against the backdrop of the findings of the managerial and organizational cognition theory and cognitive psychology. – – Investitionsentscheidungen haben einen großen Einfluss auf das Leistungsvermögen von Unternehmen. Dabei handelt es sich bei diesen Entscheidungsprozessen nicht um rationale Entscheidungen, sondern um Realitätskonstruktionen, die ihrerseits systematischen Wahrnehmungsverzerrungen (cognitive biases) unterliegen. Der vorliegende Artikel beantwortet die Frage nach verhaltenswissenschaftlichen Erfolgsfaktoren für Investitionsent-scheidungsprozesse. Reflektive Vorsicht, kritische Kommunikation und Ergebnisunabhängigkeit werden als entscheidende Faktoren im fünfphasigen Investitionsprozess identifiziert und vor dem Hintergrund der Erkenntnisse der angewandten Kognitionswissenschaften und der kognitiven Psychologie diskutiert. Der Artikel ist in englischer Sprache verfasst.
Keywords: 650; Investitionsrechnung; Verhaltensökonomik; Kognition; Erkenntnistheorie; Organisationale Entscheidung